Penerapan Metode Analytical Hierarchy Process Dalam Menentukan Prioritas Penanganan Jalan di Kota Palangka Raya - Mister Dody; Sutan P. Silitonga; Murniati (Jurnal Serambi Engineering, 2024)
Due to the increasing community activities, vehicle traffic flow and road life, road conditions in Palangka Raya City have decreased due to the rapid expansion of the area. By using the Analytical Hierarchy Process (AHP) technique, this thesis attempts to determine the criteria for the significance weight of variables in the priority of road management in Palangka Raya City, especially on national roads, provincial roads and city roads. Factors such as land use, accessibility, mobility, traffic volume and road damage are considered. Data was collected through interviews and questionnaires and analysed using AHP with Expert Choice software. Based on this study, the most important national road in Palangka Raya City is Jalan Tjilik Riwut, followed by Jalan RTA Milono, Jalan Adonis Samad and Jalan Imam Bonjol. Jalan A Yani, Jalan Yos Sudarso, Jalan George Obos and Jalan Seth Adji are provincial roads in order of priority. While for city roads, the priority order is as follows: Jalan Temanggung Tilung, Jalan Galaxy Raya, Jalan Garuda and Jalan Tingang. The Consistency Ratio (CR) values for national, provincial and city roads are 0.02, 0.03 and 0.02 respectively.